DEVELOPING BUSINESS STRATEGY THROUGH SWOT ANALYSIS OF KRAKATOA NIRWANA DEVELOPMENT - Mawardi, Izhari; Yasmine, Anbiya (Academic Research Centre Services, 2018)
Krakatoa Nirwana Development (PT. KND) is one of the subsidiaries of Bakrieland, an integrated property company. As the developer of Krakatoa Nirwana Resort (KNR), PT. KND has established the zone development plan for KNR further expansion due to the rapid growth of tourists visit to Lampung and government concerns in developing infrastructure and boosting the tourism sector. The purpose of this study is to determine the SWOT analysis of PT. KND in accordance with the KNR development, to analyze its zone development as a form of strategy, and to determine the recommendations in achieving the zone development as a form of strategy. This research was formulated by conducting in-depth interview, field observation, and using triangulation as the validity tool. PT. KND was involved in almost every data collection and analysis part. Findings show that zone development is not quite suitable in accordance with the external and internal factor. In conclusion, a set of suggestion was given to solve problems that might come from external and internal factors. Also, the best strategy was recommended in order to support KNR operational and development.